HUBUNGAN JOB DEMAND, JOB CONTROL, DUKUNGAN SOSIAL DAN FAKTOR INDIVIDU TERHADAP STRES KERJA PADA PENDAMPING SOSIAL PKH KOTA BEKASI - Kusuma, Aditya Maula; Wahyuni, Ida; Widjasena, Baju (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Stress can be described when there is a gap between individual needs and capabilities which resulted in individual stress. Work stress can be caused by high workload. The purpose of this research is to analyze the relationship between job control, job demand, sosial support, and individual factors on work stress in the Sosial Assistance Program Keluarga Harapan (PKH) in Bekasi The method of this research is descriptive observational with a cross-sectional study design. The dependant variable is work stress, whereas the independent variables are age, marital status, self-efficacy, number of children, job demand, job control, and sosial support. The population of this study is 117 workers and the number of samples is 60 women. Measurement of work stress used the General Health Questionnaire (GHQ-12). The statistical analysis used the Chi-Square test. he results indicate that there are variables related to work stress, namely the number of children (p = 0.006), self-efficacy (p = 0.003), job demand (p = 0.006), and job control (p = 0.047). However, age (p-value = 0.366), marital status (p = 0.260), and sosial support (p = 0.156) are not related to work stress. Based on the result of the study, the institution should do applicable and impactful efforts to deal with work stress events, for example the institution can arrange a special event for sharing between institution, coordinators, and workers regarding the number of work demands and submission deadlines.